MONITORING IN THE SYSTEM OF LONG-TERM TRAINING OF HIGHLY QUALIFIED ATHLETES AND SPORTS RESERVES (World Science, 2020)
The article considers modern views on the organization and conduct of regular monitoring in the field of physical culture and sports, in particular in the system of long-term training of highly qualified and young athletes. The paper presents a problematic review of monitoring in the long-term system of training athletes. The main aspects of monitoring in the system-structural approach in the preparation of high-class athletes are presented and the effectiveness of solving this issue in the management of athletes ' training during the training process and competitive activities is shown.